2007
DOI: 10.1002/bit.21357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calcium on microbial reduction of solid phase uranium(VI)

Abstract: The effect of calcium on the dissolution and microbial reduction of a representative solid phase uranyl [U(VI)], sodium boltwoodite (NaUO(2)SiO(3)OH . 1.5H(2)O), was investigated to evaluate the rate-limiting step of microbial reduction of the solid phase U(VI). Microbial reduction experiments were performed in a culture of a dissimilatory metal-reducing bacterium (DMRB), Shewanella oneidensis strain MR-1, in a bicarbonate medium with lactate as electron donor at pH 6.8 buffered with PIPES. Calcium increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…These results parallel biological reduction of U(VI), in which bacteria use U(VI) as a terminal electron acceptor in metabolism (Lovley et al, 1991). In these systems, it has been shown that bacteria can reduce U(VI) when in the form of U(VI)-CO 3 aqueous complexes, but the presence of Ca inhibits U(VI) reduction (Brooks et al, 2003;Liu et al, 2007;Stewart et al, 2007). In the case of surface-catalyzed heterogeneous reduction, inner-sphere sorption is thought to proceed U(VI) reduction (Charlet et al, 1998;Ilton et al, 2004;Scott et al, 2005).…”
Section: Long-term U(vi)-chlorite Exposurementioning
confidence: 82%
“…These results parallel biological reduction of U(VI), in which bacteria use U(VI) as a terminal electron acceptor in metabolism (Lovley et al, 1991). In these systems, it has been shown that bacteria can reduce U(VI) when in the form of U(VI)-CO 3 aqueous complexes, but the presence of Ca inhibits U(VI) reduction (Brooks et al, 2003;Liu et al, 2007;Stewart et al, 2007). In the case of surface-catalyzed heterogeneous reduction, inner-sphere sorption is thought to proceed U(VI) reduction (Charlet et al, 1998;Ilton et al, 2004;Scott et al, 2005).…”
Section: Long-term U(vi)-chlorite Exposurementioning
confidence: 82%
“…More important in the framework of this study with regard to the biosphere is the fact that the predominant presence of this carbonato calcic uranium complex in seawater, most often not identified, would explain different phenomena such as the weak integration of uranium in green algae (Chlamydomonas reinhardtii) 55 or the important limitation observed in the microbiological reduction of U(VI) (order of magnitude) due to the presence of calcium. 56,57 Moreover, it has been shown that speciation of uranium in Benthic Foramifera as a proxy for the deep sea carbonate saturation is directly dependent on the carbonate concentration and on the uranium/calcium (from the shell) ratio. 58 Lately, the study of the biosorption of U(VI) by the marine bacterium Idiomarina loihiensis showed that more complex phases including phosphate ones together with calcium may also occur.…”
Section: Speciation Modelling In Seawatermentioning
confidence: 99%
“…Monodentate phosphate binding, accompanied by extensive bridging, is commonly observed in experimental X-ray crystal structures of uranyl and other actinide phosphate complexes and minerals, resulting in great structure diversity and extended networks. Mineralization has been considered as an approach to produce actinide phosphates as matrices for long-term radioactive waste storage. Biological organisms can accumulate and precipitate uranyl ions from the environment. EXAFS measurements of the nature of the uranyl complexes formed at the surfaces of Bacillus cereus and Bacillus sphaericus cells and spores showed that uranium binding primarily occurs at the phosphoryl residues on the cell walls of these Gram-positive residues, mainly in a monodentate fashion. It was suggested that lipopolysacharides and phospholipids within the bacterial cell wall can also provide phosphoryl groups for metal ion binding. …”
Section: Introductionmentioning
confidence: 99%